2019
DOI: 10.1111/mec.15281
|View full text |Cite
|
Sign up to set email alerts
|

Angiosperm to Gymnosperm host‐plant switch entails shifts in microbiota of theWelwitschiabug,Probergrothius angolensis(Distant, 1902)

Abstract: The adaptation of herbivorous insects to new host plants is key to their evolutionary success in diverse environments. Many insects are associated with mutualistic gut bacteria that contribute to the host's nutrition and can thereby facilitate dietary switching in polyphagous insects. However, how gut microbial communities differ between populations of the same species that feed on different host plants remains poorly understood. Most species of Pyrrhocoridae (Hemiptera: Heteroptera) are specialist seed‐feeder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…While insect species was the strongest driver of structure and diversity of bacterial communities in this study, diet also showed a significative effect. Several previous studies showed that insect‐associated microbial communities are often shaped by their host's diet, for example in termites (Mikaelyan et al, 2015), aphids (Holt et al, 2020; Wu et al, 2018; Xu et al, 2019, 2020), bugs (Martinez et al, 2019), beetles (Kim et al, 2017), fruit flies (Asimakis et al, 2019; Majumder et al, 2019; Malacrinò et al, 2018; Woruba et al, 2019), soldier flies (Bruno et al, 2019) and ants (Russell et al, 2009). Interestingly, the bacterial communities associated with Phtorimaea operculella varied even according to the plant tissue insects were feeding on (Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While insect species was the strongest driver of structure and diversity of bacterial communities in this study, diet also showed a significative effect. Several previous studies showed that insect‐associated microbial communities are often shaped by their host's diet, for example in termites (Mikaelyan et al, 2015), aphids (Holt et al, 2020; Wu et al, 2018; Xu et al, 2019, 2020), bugs (Martinez et al, 2019), beetles (Kim et al, 2017), fruit flies (Asimakis et al, 2019; Majumder et al, 2019; Malacrinò et al, 2018; Woruba et al, 2019), soldier flies (Bruno et al, 2019) and ants (Russell et al, 2009). Interestingly, the bacterial communities associated with Phtorimaea operculella varied even according to the plant tissue insects were feeding on (Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared with PxR, both PxP-1 and PxP-17 harbored abundant Enterococcaceae. Enterococcaceae can facilitate seed consumption in Harpalus pensylvanicus [ 31 ], reduce gut pH [ 32 ] and increase immunity [ 33 ] in Bombyx mori , provide nutrients for Spodoptera littoralis [ 34 ], and protect lepidopterans from Bacillus thuringiensis [ 35 ]. PxP-17 was associated with a decrease in Lachnospiraceae, which metabolize plant polysaccharides [ 36 ] and reduce graft-versus-host disease mortality [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…While insect species was the strongest driver of structure and diversity of bacterial communities in this study, diet also showed a significative effect. Several previous studies showed that insect-associated microbial communities are often shaped by their host's diet, for example in termites (Mikaelyan et al, 2015), aphids (Wu et al, 2018;Xu et al, 2019Xu et al, , 2020Holt et al, 2020), bugs (Martinez et al, 2019), beetles (Kim et al, 2017), fruit flies (Malacrinò et al, 2018;Majumder et al, 2019;Woruba et al, 2019;Asimakis et al, 2019), soldier flies (Bruno et al, 2019) and ants (Russell et al, 2009). Interestingly, the bacterial communities associated with Phtorimaea operculella varied even according to the plant tissue insects were feeding on (Zheng et al, 2020).…”
Section: Response Of Bacterial Clades To Factors Influencing Insect Microbial Communitiesmentioning
confidence: 99%